APPLICABILITY OF COMPETENCE BASED EDUCATION AND TRAINING CURRICULUM AND ACQUISITION OF EMPLOYABLE SKILLS AMONG VISUALLY IMPAIRED LEARNERS IN TVET INSTITUTIONS IN KENYA - Mutua, Priscillah Nduku; Kimiti, Richard; Mulwa, David (Scholarly Research Journal for Interdisciplinary Studies, 2019)
According to the Kenyan Vision 2030,Technical and Vocational Education play a pivotal role in the social and economic development of a country. The objective of this study was todetermine the influence of competence based education and training curriculum on acquisition of employable skills among visually impaired learners in TVET institutions in Kenya.The study applied a mixed methods research design. The study targeted 2 principals, 20 heads of departments, 70 trainers, 150 visually impaired learners and graduates of Machakos Technical Institute for the Blind and Sikri Technical Training Institute for Deaf-Blind, 2 Ministry of Education officials in charge of TVET, Curriculum Development Accreditation and Certification Council officials, 3 Ministry of Labour officials, 10 members of civil society groups and 5 managers of industries. A census of the principals and trainers was taken while purposive sampling was used to sample the rest of the respondents. Primary data was collected using questionnaires, interview schedules, focused group discussion guide and observation checklists. Quantitative data was analyzed using descriptive and inferential statistics while qualitative data was analyzed using content analysis.The study found that applicability of CBET curriculum positively and significantly influenced the acquisition of employable skills among the visually impaired learners in TVET institutions in Kenya. The study further found out that core competencies as stipulated in the curriculum were the most challenging competencies to impart to the visually impaired learners when compared to basic and common competencies. This supported by the finding that quite a number of learners in the institutes were not declared competent at the end of their course work.The study therefore concluded that the level of acquisition of employable skills among the visually impaired learners in TVET institutions was considerably affected by the level of applicability of the CBET curriculum. The study recommends that curriculum developers should allocate more time for learning for the visually impaired learners as this could perfect their competencies and adaptation of the curriculum to meet their needs and consider their difficulties
Keywords: Applicability; competence based education and training curriculum; employable skills; visually impaired learners; visually impaired learners